Associations of choroid plexus volume with white matter hyperintensity volume and susceptibility and plasma amyloid markers in cerebral small vessel disease - Pengcheng Liang; Meng Li; Yiwen Chen; Zhenyu Cheng; Na Wang; Yuanyuan Wang; Nan Zhang; Yena Che; Jing Li; Changhu Liang; Lingfei Guo (Alzheimer’s Research & Therapy)
Abstract Background White matter hyperintensity (WMH) is a key feature of cerebral small vessel disease (CSVD). The impact of the choroid plexus (CP) volume on disease progression remains largely unexplored. This study evaluated the relationship between CP volume and CSVD severity via WMH volume and susceptibility values. Additionally, we explored whether Alzheimer's disease (AD)-related plasma proteins influence the volume of the CP. Methods and materials Our study included 291 CSVD individuals, with 84 participants completing subsequent brain MRI at a mean follow-up of 20 months. To explore the potential CP-associated pathways, we assessed the relationships between AD-related plasma biomarkers and CP volume via multiple linear regression analysis. The longitudinal associations between CP volume and WMH characteristics (WMH volume and susceptibility) were analyzed via linear mixed-effects models. Finally, we employed random forest analysis with the Boruta algorithm to identify key predictors of CSVD severity. Results Plasma Aβ1‒40 levels were positively correlated with CP volume (β = 0.115, P = 0.009), whereas Aβ42‒40 ratio were negatively associated with CP volume (β = -0.135, P = 0.03). Notably, increased CP volume was associated with both greater WMH burden (β = 0.191, P = 0.011) and decreased WMH susceptibility (β = -0.192, P = 0.012). Furthermore, random forest modeling identified CP volume and WMH susceptibility as the strongest predictors of CSVD severity. Conclusions CP volume changes were significantly correlated with both WMH volume and WMH susceptibility in CSVD patients. These findings suggest that CP-mediated pathways may link amyloid metabolism to CSVD progression.